STRUCTURAL ANALYSIS INCLUDING THERMAL EFFECTS FOR ICEBREAKERS. - Kiesling,Ernst W. (1967)
The report gives the results of a study conducted by the Structural Research Department of Southwest Research Institute for the United States Coast Guard. The study consisted of an analytical analysis of a three-dimensional structural model based on an existing icebreaker of the 'WIND' class. The effects on stresses and deformations of temperature variation through the structure are examined through the use of the computer program FRAN. (Author)